2001
DOI: 10.4049/jimmunol.166.2.1214
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 Adenoviral Gene Therapy Reduces Inflammation, Proinflammatory Cytokines, Vascularization, and Bony Destruction in Rat Adjuvant-Induced Arthritis

Abstract: IL-4 is a cytokine with anti-inflammatory properties on activated macrophages. Rheumatoid arthritis, an autoimmune inflammatory disease, is characterized by a paucity of IL-4 and an abundance of synovial macrophage-derived mediators. Herein, the effect of a single injection of adenovirus-producing rat IL-4 (AxCAIL-4) or a control virus with no inserted gene was compared with the effect of PBS injection into rat ankles. Ankles were injected before arthritis onset or at maximal inflammation. Preventatively, AxCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 35 publications
4
91
1
1
Order By: Relevance
“…44 Upon sacrifice on day 18, rat ankles were removed and immediately put on ice, and then radiographic examinations were performed. Radiographs were scored on the joint space change, degree of bony destruction and the soft tissue swelling, and all scores were summed up with a total scale from 0 to 10.…”
Section: Clinical and Radiological Evaluation Of Lentivirus-mediated mentioning
confidence: 99%
See 1 more Smart Citation
“…44 Upon sacrifice on day 18, rat ankles were removed and immediately put on ice, and then radiographic examinations were performed. Radiographs were scored on the joint space change, degree of bony destruction and the soft tissue swelling, and all scores were summed up with a total scale from 0 to 10.…”
Section: Clinical and Radiological Evaluation Of Lentivirus-mediated mentioning
confidence: 99%
“…Radiographs were scored on the joint space change, degree of bony destruction and the soft tissue swelling, and all scores were summed up with a total scale from 0 to 10. 44 …”
Section: Clinical and Radiological Evaluation Of Lentivirus-mediated mentioning
confidence: 99%
“…Endogenous IL-4 is thought to inhibit development of arthritis, but it has not been proven to present this effect [21]. Studies performed with a group of trauma victims showed a possible correlation between IL-4/-589 polymorphism and its stimulating action on the Th2 immune response, with development of a severe picture of systemic inflammatory response in these subjects.…”
Section: Anti-inflammatory Cytokines In the Context Of Sepsismentioning
confidence: 99%
“…It is produced and regulated mainly by Th2 cells, mast cells, and basophils. In vitro experiments have shown that IL-4 acts on monocytes, inhibiting production of inflammatory cytokines, such as TNF-a, IL-1a, IL-1b, IL-6, and IL-8 [21]. Its protective antiinflammatory effect in chronic illness -such as diabetes mellitus and rheumatoid arthritis -is being investigated, opening possibilities for its role as a potential factor in the treatment of auto-immune diseases [21][22].…”
Section: Interleukin-4 (Il-4) Mast Cells T Cells and Stomatal Cellsmentioning
confidence: 99%
“…Synovial tissues taken from the ankle joints of rats with CIA on day 27 were snap frozen and homogenized, as described previously (32). The levels of MIP-1␣, IL-1␤, and TNF-␣ in the ankle homogenates were quantified using ELISA kits (R&D Systems), according to the manufacturer's instructions.…”
Section: Elisamentioning
confidence: 99%